Five Graphic Music Analyses - Schenker, Heinrich 1868-1935 (New York Dover, 1969)
Schenker's structural analysis differentiates between harmonic and contrapuntal functions of chords, emphasizing the relative significance of all tones in terms of motion and direction in the achievement of organic tonal unity. These sketches study the musical architecture of two works by Bach, a developmental section by Haydn, and a pair of ètudes by Chopin.